Adsorption of Nickel Ions on Oxygen‐Functionalized Carbons. Issue 4 (26th February 2016) - Kern, Andreas M.; Zierath, Bodo; Fey, Tobias; Etzold, Bastian J. M.
Abstract: The adsorption of nickel(II) ions on pristine and wet‐chemically oxidized microporous carbons is studied. The nature and acidity of the resulting oxygen functional groups are characterized by temperature‐programmed desorption and point of zero charge measurements. The maximal nickel ion adsorption capacity of the resulting high‐affinity Langmuir‐type adsorption equilibrium is strongly influenced by the oxidative pretreatment. At maximum, loadings of 7.5 wt % could be obtained for carbons showing oxygen content of 12.5 mmol g −1 . A linear correlation of the ion uptake with the surface oxygen content could be deduced. In a kinetic study, it could be proved that the uptake of nickel at room temperature is a slow process and that the time for adsorption is independent of oxygen content, carbon type, and nickel loading. Abstract : The adsorption equilibria and kinetics of nickel(II) ions were studied for several oxidized carbons. Nature and quantity of surface groups were investigated by temperature‐programmed desorption. The results allowed the deduction of a general linear correlation between nickel uptake and surface oxygen content as well as guidelines for the required adsorption.